2021
DOI: 10.31949/jcp.v7i2.2878
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Nature of Sains (Nos) Sebagai Metode Terhadap Peningkatan Pemahaman Hakikat Sains Siswa Sekolah Dasar

Abstract: This research is backround by understanding the nature of science (NOS) which is very important to be taught in science learning, science learning in elementary schools still has not taught science with NOS and research on understanding NOS has so far been carried out on teachers and few on students. This study purposeds to determine differences in the understanding of primary school students' NOS before and after using the NOS learning model as a method, to determine the response to understanding NOS in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…A defining characteristic of scientific knowledge is its empirical foundation, built upon a robust bedrock of experimental data and observational evidence garnered through rigorous scientific methodologies (Kuo et al, 2018;Radder, 2021). However, generating scientific knowledge is not an entirely objective undertaking (Nurhayati & Widodo, 2021). It is also shaped by myriad personal and societal factors, thereby introducing an element of subjectivity into the process (Messas, 2017).…”
Section: Introduction Background Of the Studymentioning
confidence: 99%
“…A defining characteristic of scientific knowledge is its empirical foundation, built upon a robust bedrock of experimental data and observational evidence garnered through rigorous scientific methodologies (Kuo et al, 2018;Radder, 2021). However, generating scientific knowledge is not an entirely objective undertaking (Nurhayati & Widodo, 2021). It is also shaped by myriad personal and societal factors, thereby introducing an element of subjectivity into the process (Messas, 2017).…”
Section: Introduction Background Of the Studymentioning
confidence: 99%
“…The application of learning models in PJOK is expected to be able to increase student attention, motivate students to enthusiastically carry out activities in the PJOK learning process and can benefit in the form of values tucked away during learning, especially attitude values (Agustryani, 2020). (Indrayogi, 2022) revealed that providing the right learning model to increase students' understanding of movements in jumsihat gymnastics. One of them is by using an inquiry learning model.…”
mentioning
confidence: 99%
“…Meningkatkan minat dan hasil belajar IPS melalui powerpoint dan inquiry based learning (Hartini, Nugrahani & Giyatno, 2022). Model pembelajaran inkuiri terhadap peningkatan pamahaman konsep gerak senam jumsihat (Indrayogi & Nurhayati, 2022). Belum adanya kajian tentang model pembelajaran inkuiri dan minat belajar terhadap hasil belajar bola voli peserta didik.…”
unclassified